Aquaporin as a membrane transporter of hydrogen peroxide in plant response to stresses - Jang, Ji Young (Landes Bioscience, 2012)
Hydrogen peroxide (H(2)O(2)) is a reactive oxygen species that signals between cells, and H(2)O(2) signaling is essential for diverse cellular processes, including stress response, defense against pathogens, and the regulation of programmed cell death in plants. Although plasma membrane intrinsic proteins (PIPs) have been known to transport H(2)O(2) across cell membranes, the permeability of each family member of PIPs toward H(2)O(2) has not yet been determined in most plant species. In a recent study, we showed that certain isoforms of Arabidopsis thaliana AtPIPs, including AtPIP2;2, AtPIP2;4, AtPIP2;5, and AtPIP2;7, are permeable for H(2)O(2) in yeast cells. Since the expression of PIPs is differently modulated in Arabidopsis by abiotic stress or H(2)O(2) treatment, it is important to investigate the integrated regulation of aquaporin expression and their physiological significance in H(2)O(2) transport and plant response to diverse abiotic stresses.